The Role Of Sharia Banking To Recover Smes During Covid-19 Pandemic - Rudiaman, Rudiaman; Nasser Hasibuan, Abdul; Hardana, Ali; Efendi Siregar, Sulaiman (Fakultas Ekonomi dan Bisnis Islam, 2022)
The purpose study to determine development sharia banking financing for SMEs during covid-19 pandemic. Then to find role sharia banking recover SMEs during covid-19 pandemic. Type research used library research, data source used secondary data, which has published institutions processed researchers and from various pre-existing sources. Data analysis technique used research descriptive qualitative, describing development financing sharia banking and role of sharia banking for recovery SMEs during covid-19 pandemic. Results showed development of financing in sharia banking was distributed SMEs during covid-19 pandemic experienced decrease amount of financing. Largest decline in financing occurred in BPRS financing for SMEs, which experienced decline of 14.88 percent, BUS financing investment SMEs decrease 14.17 percent, and UUS financing decrease 13.47 percent. Role sharia banking recovery SMEs during covid-19 pandemic is increasing portion financing SMEs, assisting them players as partners, sharia banking can provide payment, increasing number financing profit-sharing schemes more appropriate for financing SMEs.